Time in Context - Harry, Chelsea C. (Chronos in Aristotle’s Physics: On the Nature of Time, 2015)
The key to taking in Aristotle’s treatise on time is to approach it with the understanding that Aristotle was not a philosopher concerned with time —in questions about time or in delimiting the being of time.
Citation Key Alias: lens.org/039-932-676-491-061
Keywords: Accidental Change; Accidental Form; Natural Object; Predicative Change; Privative Form; dept.phi

Physics iv 10-11 as a Parallel Account - Harry, Chelsea C. (Chronos in Aristotle’s Physics: On the Nature of Time, 2015)
Given the context of the Physics just explored, it will not be a surprise if time (chrόnos) in Aristotle’s analytic of time turns out to be not a being qua itself but an attribute of motion, an interval.
Citation Key Alias: lens.org/010-220-856-100-488
Keywords: Infinite Divisibility; Infinite Time; Internal Inconsistency; Natural Object; Underlying Unity; dept.phi

Chronos in Aristotle's Physics: On the Nature of Time - Harry, Chelsea C. (Springer, 2015)
Keywords: Aristotle. Physics; Time; Philosophy; Philosophy of nature; Philosophy; Physics; dept.phi; faculty_collection